EFEKTIVITAS SISTEM FILTRASI MENGGUNAKAN MEDIA FILTRASI YANG BERBEDA DALAM PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU DI DESA PENEDAGANDOR: EFEKTIVITAS SISTEM FILTRASI MENGGUNAKAN MEDIA FILTRASI YANG BERBEDA DALAM PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU DI DESA PENEDAGANDOR - RIZKY AULIA HUSNIATI; muliadi putra agus; Husnayati Hartini (Jurnal Teknologi Lingkungan, 2025)
The tofu industry produces high-strength wastewater that contains large amounts of organic pollutants such as BOD and COD. Direct disposal of untreated wastewater leads to environmental degradation, especially in water bodies. This study aims to determine the effectiveness of a filtration system using activated carbon media compared to a system without activated carbon in reducing BOD, COD, and pH levels in tofu wastewater in Penedagandor Village. The experiment used two filtration units with different media compositions. Parameters analyzed were BOD, COD, and pH. The results indicated that the filtration system with activated carbon was more effective in reducing organic pollutants. The BOD reduction ranged from 47.57–83.71% with activated carbon and 43.47–77.46% without activated carbon. COD reduction ranged from 14.24–51.59% with activated carbon and 10.05–46.23% without activated carbon. pH remained within acceptable limits of 6–9. ANOVA analysis revealed significant differences in BOD and COD between treatment methods, while pH differences were not significant